Servant leadership, innovative work behavior and innovative organizational culture: The mediating role of perceived organizational support - Ekmekcioglu, Emre Burak; Öner, Kürşad (European Journal of Management and Business Economics (EJM&BE), 2024)
Purpose - The purpose of this study is to examine the effects of servant leadership (SL) and innovative organizational culture (IOC) on employees' innovative work behavior (IWB). In addition, this paper attempts to examine the mediating role of perceived organizational support (POS) in these relationships. Design/methodology/approach - Data were collected from 280 employees working in technopark companies located in Turkey, which require intensive IWB. Structural equation modeling and bootstrapping procedure were used to test the hypothesized relationships. Findings - The findings suggest that SL, and IOC are significantly and positively related to employees' IWB. The results also show that SL and IOC stimulate employees' IWB through POS. Research limitations/implications - Because this study was carried out by employing a cross-sectional research design with data obtained from the same source, the inferences about the causality among the variables cannot be inferred. Practical implications - The empirical findings suggest that organizations should make efforts to promote SL and improve IOC in order to harvest IWB from their employees. Moreover, organizations and managers need to recognize the importance of the POS by employees, and therefore form an adequate working environment, create and utilize policies and procedures accordingly. Originality/value - This study suggests ways for organizations to enhance their innovativeness through IOC and SL applications in pursue of harvesting employees' IWB using POS by employees as mediator. This study is also original, in that no previous studies have investigated the mediating role of POS in the relationship between IOC, SL and IWB.